Health education to stds prevention and responsible sexuality (Revista Venezolana de Salud Pública, 2021)
Sexually Transmitted Diseases (STDs) are important pathologies in public health, with young people being a vulnerable group worldwide, due to the frequent exercise of an early, unreflective and reckless sexuality. The objective of the research was to analyze the impact of health education on the prevention of sexually transmitted ++diseases and the exercise of responsible sexuality, considering the knowledge, culture and sexual practices of nursing students of the first regular academic period 2019 from the Instituto Superior Tecnologico Libertad. The research had a quantitative approach, a non-experimental, descriptive design, with a cross-sectional field modality. The sample was intentional, of 240 students, to whom surveys were applied before and after the educational interventions. As a relevant result, it was obtained that 35.7% began their sexual activity between 15 and 18 years, the level of knowledge on the subject increased from 8% to 12%, there is resistance on the part of women to the use of condom, and only 69% of men use it. Regarding the issue of sexuality, this is partially addressed between parents and young people, there is a tendency to hidden couple relationships, and to sexual practice with several partners. Conclusions: The level of knowledge about STDs improves significantly, however, doubts remain. The lack of confidence in sexuality issues, hidden partner relationships and the tendency not to carry out routine medical check-ups were maintained. This implies considering more complex intervention strategies that involve public health policies aimed at education and the development of responsible sexuality.
Keywords: Health education; Knowledge; Responsible Sexuality; Sexually Transmitted Diseases